2010
DOI: 10.1063/1.3352422
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact ionization of furanose alcohols

Abstract: Electron impact ionization of the gas phase 3-furanol, tetrahydro (3-hydroxytetrahydrofuran, 3HTHF) and 2-furanmethanol, tetrahydro (alpha-tetrahydrofurfuryl alcohol, THFA) molecules has been studied both experimentally and theoretically. The electron induced positive ion formation has been investigated experimentally using a crossed electron/neutral beams technique in combination with a quadrupole mass spectrometry. The mass spectra of both molecules have been determined at the incident electron energy of 70 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The present measured results are also in good agreement with the appearance energy measured for the THFA parent cation of 9.43 ± 0.12 eV (Ref. 48) and with previous photoelectron spectroscopy measurements. 45 The calculated momentum density probability distribution for the HOMO of THFA is presented in Figure 3.…”
Section: Resultssupporting
confidence: 81%
“…The present measured results are also in good agreement with the appearance energy measured for the THFA parent cation of 9.43 ± 0.12 eV (Ref. 48) and with previous photoelectron spectroscopy measurements. 45 The calculated momentum density probability distribution for the HOMO of THFA is presented in Figure 3.…”
Section: Resultssupporting
confidence: 81%
“…Note that the above procedure is identical to that used in our recent work [54]. If we were to use equation 1, instead of equation 2, for the experimental data fitting, then the resultant fits give slightly higher values of the appearance energy, as shown in ref [69]. The appearance energy of argon (15.759 eV) [66] was used to calibrate the energy scale.…”
Section: Experimental Methods Data Analysis and Theoretical Detailsmentioning
confidence: 99%
“…However, significantly less experimental and theoretical effort has been devoted to THFA compared to THF. 5,10,13 The scattering data for THFA that is presently available in the literature (electron, positron, and photon) includes some independent atom method (IAM) elastic cross sections and binary-encounter Bethe (BEB) total ionisation cross sections, 14 a total cross section (TCS) measurement from Możejko et al, 15 some elastic DCS data 16 at intermediate to high energies, a dissociative ionisation study from Milosavljević et al, 17 and some dynamical (e,2e) investigations from Bellm et al 18 and Jones et al 19 More recently, a detailed study into electronic-state electron impact excitation (20-50 eV) in THFA has been advanced by Duque et al 12 and Chiari et al 20 We note that those latest investigations 12,20 also included IAM with screened additivity rule (SCAR) correction computations for elastic DCS and ICS and the TCS in THFA. From a positron perspective, we only know of the TCS measurement from Zecca et al 21 Photoionisation cross sections are also available, 11,22 as are photoabsorption cross sections from the very recent measurement of Limão-Vieira et al 11 That latter paper also contains a set of comprehensive electronic-structure calculations, which showed that of the six FIG.…”
Section: Introductionmentioning
confidence: 99%